Welcome to Bosnia and Herzegovina - Mulla-Feroze, Umaima; Gabrielpillai, Matilda; Gibbs, Dorothy L. (Milwaukee, Wis. : Gareth Stevens Pub., 2002)
An overview of the geography, history, government, economy, people, and culture of Bosnia and Herzegovina.
Includes bibliographical references (p. 47) and index.
Keywords: Bosnia and Hercegovina -- Juvenile literature; Bosnia and Hercegovina